IMPACT OF COVID-19 PANDEMIC IN THE SUPPLY CHAIN MANAGEMENT OF THE MILK TEA STORES - De Jesus, Fhrizz Saet; Buenaventura, Blisa Pacada (Accounting Department,, 2021)
Purpose — This paper assesses the impact of the Covid- 19 Pandemic in the supply chain management (SCM) of the milk tea stores in Bongabon, Nueva Ecija, Philippines. Since milk tea is a popular drink in the said area, this paper seeks to know how the owners deal with the barriers they have encountered during the pandemic. Design/methodology/approach — The study used a descriptive method using a total enumeration as the sampling technique. The respondents were fully operational milk tea store owners who encountered barriers in their SCM.Findings — In line with the barriers in the SCM, the study shows that the majority of the respondents strongly agreed that the staff is afraid of the spread of the virus (Human Resource), experienced Limited business time of operation (Enforcement of Local Rules), Limited entrants of delivery vehicle (Transportation), Instability in the supply of raw materials (Raw Materials), & Sales decrease due to pandemic (Cash flow).Practical Implications — The business operations of the respondents suffered from the effect of the covid 19 pandemics.Originality/value — This study presents the recommendation on how the business owners can cope up with the impact of this pandemic not only in their SCM but their business as a whole.Keywords Covid- 19 Pandemic, Supply Chain Management, Milk tea.Paper Type Research Paper.